Hambatan Aksesi Turki ke Uni Eropa - Ikhsan, Yozar Qohari Bil; Utomo, Tri Cahyo (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Based on political term in the Copenhagen Criteria, European Commission decide the requirements for Accession to European Union which to guarantee and protect Democracy, Human Rights and Minority Rights. Those are supported by the Liberalism perspective on international relation study which explains that regional cooperation and international cooperation can be done if the state can guarantee the enforcement of Democracy and protect the Human Rights included Minority Rights. This research purpose is to find the obstacles of the Turkey accession to European Union using Descriptive-Qualitative analysis method and Liberalism approach. This research result argues that Turkey has done many efforts for qualifying up the requirements to get the Accession to European Union immediately. But in 2010-2016 the European Union appraised Turkey hasn’t done the enforcement of Democracy, Human Rights, and Minority Rights fully yet. Then Turkey accession efforts to the European Union got an obstacle.